Cover Picture: Multi‐Enzymatic Synthesis of Optically Pure β‐Hydroxy α‐Amino Acids (Adv. Synth. Catal. 4/2015). Issue 4 (17th February 2015) - Hibi, Makoto; Kasahara, Takuya; Kawashima, Takashi; Yajima, Hiroko; Kozono, Shoko; Smirnov, Sergey V.; Kodera, Tomohiro; Sugiyama, Masakazu; Shimizu, Sakayu; Yokozeki, Kenzo; Ogawa, Jun
Abstract : The front cover picture, provided by Makoto Hibi, Jun Ogawa et al., depicts Fe(II)/α‐ketoglutarate (αKG)‐dependent dioxygenases, which are hydroxylation biocatalysts catalyzing highly selective monooxygenation available to industrial applications. Recently, a great number of Fe(II)/αKG‐dependent dioxygenases with a variety of functions has been found in the genome database, and collected into a biocatalyst library. One of these enzymes, N ‐succinylL ‐amino acid β‐hydroxylase, was applied to an enzymatic cascade system together with N ‐succinylL ‐amino acid desuccinylase for the production of optically pure β‐hydroxy α‐amino acids. Details can be found in the full paper onpages 767–774 (M. Hibi, T. Kasahara, T. Kawashima, H. Yajima, S. Kozono, S. V. Smirnov, T. Kodera, M. Sugiyama, S. Shimizu, K. Yokozeki, and J. Ogawa, Adv. Synth. Catal. 2015, 357, 767–774; DOI: 10.1002/adsc.201400672 ).